Development of elite sportsmen’s training system - Yessentayev, T.K. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2016)
Purpose: to study conditions and organizational management forms of material-technical and personnel potential’s realization in modern system of elite sportsmen’s training. Material: publications on the topic of the article were used as sources of information. Results: approaches to optimization of sportsmen’s training and competition functioning management were analyzed. In the basis of modern system of elite sportsmen’s training for competition functioning is realization of knowledge and practical experience of different specialists. Provisioning of conditions for different profiles specialists’ participation in sportsmen’s training is ensured by large training centers with developed infrastructure and wide complex of services for sportsmen. Conclusions: coordination of different profiles’ specialists in sportsmen’s preparation for competition functioning and in competition functioning is ensured by different forms of management. The most effective of them is model of chief coach’s and chief of complex scientific group’s cooperation.